2010
DOI: 10.1080/19476330903161335
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and total phenolic compounds of myrtle extracts Actividad antioxidante y contenido de compuestos fenólicos totales en extractos de myrtus

Abstract: The total phenolic content, flavonoid content and antioxidant activity of methanol, ethanol, water and ethyl acetate extracts of the leaves and berries of myrtle (Myrtus communis) were measured. Total phenolic content was assessed by the Folin-Ciocalteau assay, total flavonoid content was assessed by a colorimetric method using rutin as standard flavonoid, whereas antioxidant activity was assessed by measuring the ability of the extracts to scavenge the 2,2 0 -azinobis (3-ethylbenzothiazoline-6-sulphonic acid)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 29 publications
2
10
0
3
Order By: Relevance
“…The choice of extraction solvent is a crucial step for the assessment of antioxidant activity of extracts, since polarity of solvents determines the recovery of natural antioxidants from herbals (Goulas et al, 2012;Galanakis et al, 2013). These findings were supported by previous studies on Paramignya trimera (L.) (Nguyen et al, 2015), Opuntia ficus-indica (L.) (Ammar et al, 2015), Solanum melongena (L.) (Boulekbache-Makhlouf et al, 2013) and Myrtus communis (L.) (Amensour et al, 2010), which reported that extracts prepared by methanol solvent had higher antioxidant properties than other organic solvents used. Results of the current investigation show that acetone and diethyl ether extracts exhibited lower levels of antioxidant activity.…”
Section: Effect Of Extracting Solvent On the Antioxidant Activitiessupporting
confidence: 77%
“…The choice of extraction solvent is a crucial step for the assessment of antioxidant activity of extracts, since polarity of solvents determines the recovery of natural antioxidants from herbals (Goulas et al, 2012;Galanakis et al, 2013). These findings were supported by previous studies on Paramignya trimera (L.) (Nguyen et al, 2015), Opuntia ficus-indica (L.) (Ammar et al, 2015), Solanum melongena (L.) (Boulekbache-Makhlouf et al, 2013) and Myrtus communis (L.) (Amensour et al, 2010), which reported that extracts prepared by methanol solvent had higher antioxidant properties than other organic solvents used. Results of the current investigation show that acetone and diethyl ether extracts exhibited lower levels of antioxidant activity.…”
Section: Effect Of Extracting Solvent On the Antioxidant Activitiessupporting
confidence: 77%
“…A oxidação lipídica é considerada a deterioração mais importante que ocorre nos alimentos, pois afeta sua qualidade -principalmente o aroma, o sabor e o valor nutricional -e resulta na produção de compostos tóxicos (Amensour et al, 2010). Assim, tendo em vista a proteção dos ovos contra os efeitos da oxidação lipídica, algumas pesquisas têm sido realizadas com antioxidantes sintéticos e naturais na alimentação das aves (Hayat et al, 2010).…”
Section: Introductionunclassified
“…Embora o processo oxidativo em ovos não seja visto como um problema, o aumento da produção de ovos enriquecidos com ácidos graxos poli-insaturados pode aumentar a suscetibilidade à peroxidação. Portanto, há necessidade de estudos que visem ao retardamento desse processo (Radwan et al, 2008;Hayat et al, 2010).A oxidação lipídica é considerada a deterioração mais importante que ocorre nos alimentos, pois afeta sua qualidade -principalmente o aroma, o sabor e o valor nutricional -e resulta na produção de compostos tóxicos (Amensour et al, 2010). Assim, tendo em vista a proteção dos ovos contra os efeitos da oxidação lipídica, algumas pesquisas têm sido realizadas com antioxidantes sintéticos e naturais na alimentação das…”
unclassified
“…Finally, A. absinthium extracts can be novel active drug compounds, as they have antiproliferative, antioxidant, and radical scavenging properties, however additional studies need to be undertaken to carry out the in vivo pharmacological experimentation of this plant [22]. Antioxidants, molecules with a radical scavenging capacity, are considered to exercise a defensive consequence against free radical injury and these molecular components may prevent many chronic diseases like cancer, hepatitis, asthma, atherosclerosis, arthritis, heart disease, and diabetes [70,71]. Currently, many synthetic antioxidants are also used, however these antioxidants have been thought to damage the liver and cause cancer [72].…”
Section: The Total Phenolic Compounds Content and Radical Scavenging mentioning
confidence: 99%